A blueprint for strengthening climate and health literacy through professional adaptability - Grabow, Maggie L.; Stull, Valerie J.; Hahn, Micah B.; Limaye, Vijay S. (Frontiers in Public Health, 2023)
Responding effectively to intensifying climate change hazards to protect human health in personal and professional settings is an urgent and pressing challenge. This will require collaboration and subject matter expertise of people across the life course and occupations. In this perspective piece, we build on a previously published compilation of climate and health literacy elements to explore tangible opportunities to strengthen climate and health understanding among individuals spanning educational levels, professional settings, and societal needs. Educational materials addressing climate change and health linkages have historically focused on K-12, college, post-graduate education, and continuing medical education, with less attention devoted to reaching students in trade schools and other professional settings. Here, we outline a flexible blueprint for strengthening climate and health literacy among all people by targeting education in a way that is relevant for each age group or profession. In particular, we discuss the idea of professional adaptability as a way to design practical climate and health training for people currently in the workforce.